Organizational and strategic communication research: global trends - Ruiz-Mora, Isabel (2019)
In this book we present the latest advances made in strategic and organizational communication. Beyond traditional approaches, we propose new ways of doing and understanding communication in today’s society. We discuss situations far from the traditional path. We delve into global citizens’ problems and the way in which dialogue and participation processes are connected. The problem of evictions and the emergence of citizens as new political actors, the management of sustainability in the digital era, the development of positive communication in socially aware companies, grassroots movements in defence of public space, how resilience can shape education, the use of brands and professional associations as activists in the defence of public interests, the feminization of politics and the power of visual elements in political campaigns are some of the issues addressed in this volume. In the book, communication is considered as the strategy to raise our voices and be heard. Strategic and organizational communication takes on an activist role to create a society that is fairer and more committed to citizens. The diversity represented in this book, not only with respect to the authors’ nationalities, but also in the theoretical and empirical approaches, reflects one of the most salient features of the European Communication Research and Education Association (ECREA) and the Organizational and Strategic Communication Section’s identity.